Implementasi Evaluasi Menurut Daniel F. Stufflebeam pada Program PJJ selama Pandemi Covid-19 - Fatimatur Rohmah; Abdul Wahid; Silviatul Hasanah (Universitas Islam Negeri Walisongo, 2021)
The covid-19 pandemic is hitting Indonesia, on the other hand activities in the world of education mut keep going. In 2020 the training Center Religious (BDK) Semarang has implemented Distance Training (PJJ) online. PJJ is implemented to provide more space train employees of the Ministry of Religion in Yogyakarta and Central Java, at amid the limitation tha hit during the covid-19 pandemic. However on in practice, researched found several problems.purpose this riset is to determine the context of PJJ implementation, input, process and product. This research uses are interviews, document review and obsercation. The result of research in the input aspect in the form of a work system applied are one day work at home and one day work at the office, the curriculum is applied in the implementationof PJJ it has adjusted to the provisions of the Ministry of Religion the center, although in the implementation of teaching sometimes innovation are made. In the PJJ process, the institution has held technical guidance for all employees, so there is no gap in using technology, quantity more and more participant, but there are problems with signal difficulties and each participant are given pulses during the training. While the result achieved in the implementation of PJJ all participants passed with an average score of 90, 60. Recommendations for the institution so that the implementation of PJJ is prioritized for entered into the work program in the coming year in the form ot the number of participants and reproduced classes, as well as institutional facilities for conducting education in a manner online enhanced.